Changes in the psychosocial and clinical profiles of anorexia nervosa patients during the pandemic - Özbaran, N. Burcu; Yılancıoğlu, Hazal Yağmur; Tokmak, Sibel Helin; Yuluğ Taş, Begüm; Çek, Didem; Bildik, Tezan (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic and related control measures have increased the prevalence of anorexia nervosa(AN) and recent studies demonstrated that approximately 70% of individuals diagnosed with AN experienced deterioration in symptoms.The aim of the present study was to examine the psychosocial and clinical impacts on patients with AN during the COVID-19 pandemic. This cross-sectional study involved 35 female AN adolescents who were being treated at Ege University Child and Adolescent Psychiatry Department.To assess pre-pandemic symptom levels and daily life routines, a retrospective form utilizing the Visual Analog Scale(VAS) was employed.BMI and Clinical Global Impression(CGI) data were recorded by the interviewer for all 35 patients who consented to participate in the study.Fifteen patients successfully completed all the forms(VAS, the Children's Depression Inventory(CDI), the Screen for Child Anxiety Related Disorders Scale(SCARED), the Eating Attitudes Test, the Quality-of-Life Scale(QoLS), the Autism Spectrum Screening Questionnaire, and the Turgay DSM-4 Based Screening and Evaluation Scale for Behavioral Disorders in Children and Adolescents)online in 2022.Clinical diagnosis and progress were assessed retrospectively using The Kiddie Schedule for Affective Disorders and Schizophrenia(K-SADS).The duration of follow-up period and the number of psychiatric visits were obtained retrospectively from patient files.Retrospective data on pre-pandemic symptom levels and daily life routines were collected using the VAS. The mean age of AN patients was16.67±1.63years.Comorbid diseases were present in73.33% of patients, major depressive disorder was the most common(46.66%).Mean scores indicated moderate levels of anxiety(SCARED score:37.23±12.67) and depression (CDIscore:17.23±10.85).QoLS scores were negatively correlated with eating attitudes(r=-0.601, p=0.039).Obsession level, exercise level and screen time increased during the pandemic, while social activity, quality of education, and perception of learning decreased. BMI increased in all patients.Patients who completed the forms had a higher number of psychiatric visits compared to those who did not complete the forms(p=0.033).The mean number of clinic visits was 26.27±20.33. The results show that the COVID-19 pandemic had adverse effects on AN patients and disrupted their daily routines.These patients experienced high rates of comorbidities.The patients showed improvement in BMI scores, indicating the positive impact of treatment.These findings emphasize the need for comprehensive psychiatric care and targeted interventions for AN patients during crises like the COVID-19 pandemic.